Mollusks as a Cheap Source of Animal Protein in Sarlahi District - Karna, Ranju Rani; Shrestha, Jiwan (Nepal Journal of Science and Technology, 2007)
The cheapest source of animal protein ever known are mollusks, the non -fish commodities. They are Ghonghi (Bellamya bengalensis), Doka (Pila globosa) and Sippy (Lamellidens marginalis) harvested from rivers, lakes, swamps, ditches and pools. In accordance with very high protein content of 57.46%, 60.52% and 52.59%, they offer an energy of 337.68, 364.01 and 330.38 in Kcal/100g of meat on dry basis respectively. Besides such dietary significance, they exhibit cultural, trade and medicinal values as well. But, still acceptional rate is highly restricted among only few lower ethnic groups like Dom, Paswan, Mushar, Dhangar, Danuwar and Tharu of Sarlahi district. This scenario really obstructs the developing country like Nepal to create a healthy population. Hence an objective of the study was to focus on applicabilities of those cheaper sources of protein in daily life alongwith their acceptance. However, the chemical parameters of the Mollusk’s habitat should be studied. It will be a great help for mass production, offering an opportunity to earn livelihood. In addition to this, pearl production through Sippy(L. marginalis) will certainly be a step towards an economic boom. Nepal Journal of Science and Technology Vol. 7, 2006